How to Improve English vocabulary for Students with Autism? - Susanti, RR. Retno Dwi (International Journal of Applied Educational Research (IJAER), 2024)
A B S T R A C T Children with Autism typically have trouble speaking with others, their linguistic abilities can still grow and improve. This study aimed to determine whether teaching students with autism English vocabulary using the TEACCH technique may assist those with Autism in developing an enjoyment and excitement for learning simple English vocabulary, correctly recognizing the words, and incorrectly mentioning the terms with the appropriate pronoun. This study employs a combination of qualitative and quantitative methods for its analysis. This school offers educational services to students with Autism, mainly through the TEACCH technique for learning simple English vocabulary. The research will focus on ten children who have autism spectrum disorder as its subjects. The TEACCH approach is used in educational activities conducted with students with Autism who speak English. This method incorporates both the photograph and the actual object. An initial test, a follow-up test, and an observation sheet collected the data. Several exercises are carried out in English learning vocabulary activities, such as pairing the object or things and mentioning the pronoun words in the appropriate context. The findings indicated that autistic students were highly interested in acquiring simple English vocabulary from other autistic students. The fact that the total Score on the post-test was 82% demonstrates that it was higher than the Score on the pre-test, which was 65.5%. They reacted appropriately and communicated effectively despite the challenges they faced. In addition, students start to take a greater interest in concentrating on their instructor.